Simulation and testing of a platooning cooperative longitudinal controller - Hapanchak, Vadym Serhiyovych (2019)
Previous studies have shown that the ITS solution called platooning allows the autonomous collaborative driving and can improve traffic safety and throughput. Traffic flow is optimized by Cooperative Adaptive Cruise Control (CACC), which allows for the automatic short-distance vehicle following, using inter-vehicle wireless communication in addition to onboard sensors. This paper presents the platooning vehicle longitudinal controller evaluation using simulation environment. The employed controller uses IEEE 802.11p technology for vehicle-to-vehicle (V2V) communications on Vehicular Ad hoc Network (VANET). To evaluate the CACC the Veins simulation framework was used and the complete simulation setup is described in this paper. The presented analysis expound the methodology to verify controller safety and stability characteristics within the different traffic scenarios and platooning maneuvers using the simulation.